If it's not what You are looking for type in the equation solver your own equation and let us solve it.
11m=13=m=23
We move all terms to the left:
11m-(13)=0
We move all terms containing m to the left, all other terms to the right
11m=13
m=13/11
m=1+2/11
| 2|x+4|=10 | | 4y+12-7=4y-2y+11 | | t/5+-59=-51 | | 15=10-5x | | 18-3x=72 | | (3+i)(3-i)=0 | | -42=x/2 | | (5-x)8=0 | | x/5+(-59)=-51 | | 16=2(x=1) | | 15x=18x-19 | | X+x-16=150 | | (8-2x)5=0 | | 10–-9h=82 | | 4-0.2x=32-x | | 16(s+19)+9=8s-4 | | 2x2+12x+20=34 | | 4(10-2x)=0 | | 5g+3g-6+18=8g+12 | | 19x-3=12-15+x | | 8c=2c+12 | | 2(x+5)-7=2(x-5) | | 2(20-4x)2=0 | | (x+-5)=7 | | 2x+120=600 | | 15/45=9/y | | 7x-5=10x-x-15x | | 3(m-52)=60 | | w-3.6=7.2 | | 7x+7-2x-1=x+4+2x-6 | | (x/2)+4x=1/3 | | 2/3x÷4/7x=–28 |